Biochemical and Expression Analyses of the Rice Cinnamoyl-CoA Reductase Gene Family - Park, Hye Lin; Bhoo, Seong Hee; Kwon, Mi; Lee, Sang-Won; Cho, Man-Ho (Frontiers in Plant Science, 2017)
Cinnamoyl-CoA reductase (CCR) is the first committed enzyme in the monolignol pathway for lignin biosynthesis and catalyzes the conversion of hydroxycinnamoyl-CoAs into hydroxycinnamaldehydes. In the rice genome, 33 genes are annotated as CCR and CCR-like genes, collectively called OsCCRs. To elucidate the functions of OsCCRs, their phylogenetic relationships, expression patterns at the transcription levels and biochemical characteristics were thoroughly analyzed. Of the 33 OsCCRs, 24 of them encoded polypeptides of lengths similar to those of previously identified plant CCRs. The other nine OsCCRs had much shorter peptide lengths. Phylogenetic tree and sequence similarities suggested OsCCR4, 5, 17, 18, 19, 20, and 21 as likely candidates for functional CCRs in rice. To elucidate biochemical functions, OsCCR1, 5, 17, 19, 20, 21 and 26 were heterologously expressed in Escherichia coli and the resulting recombinant OsCCRs were purified to apparent homogeneity. Activity assays of the recombinant OsCCRs with hydroxycinnamoyl-CoAs revealed that OsCCR17, 19, 20 and 21 were biochemically active CCRs, in which the NAD(P)-binding and NADP-specificity motifs as well as the CCR signature motif were fully conserved. The kinetic parameters of enzyme reactions revealed that feruloyl-CoA, a precursor for the guaiacyl (G)-unit of lignin, is the most preferred substrate of OsCCR20 and 21. This result is consistent with a high content (about 70%) of G-units in rice lignins. Phylogenetic analysis revealed that OsCCR19 and 20 were grouped with other plant CCRs involved in developmental lignification, whereas OsCCR17 and 21 were closely related to stress-responsible CCRs identified from other plant species. In agreement with the phylogenetic analysis, expression analysis demonstrated that OsCCR20 was constitutively expressed throughout the developmental stages of rice, showing particularly high expression levels in actively lignifying tissues, such as roots and stems. These results suggest that OsCCR20 is primarily involved in developmental deposition of lignins in secondary cell walls. As expected, the expressions of OsCCR17 and 21 were induced in response to biotic and abiotic stresses, such as Magnaporthe grisea and Xanthomonas oryzae pv. oryzae (Xoo) infections, UV-irradiation and high salinity, suggesting that these genes play a role in defense-related processes in rice.